Best Practice – Strategi Memulai Bisnis Bagi Mahasiswa Sekolah Tinggi Ilmu Ekonomi YPUP Makassar - Cipta C. Perdana; Asriah Syam; Carolina N. Mustikarini; Novika A. Triani; Sinar D. Putra; Justin Wijaya; Winarto Poernomo (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Entrepreneurship education in Indonesian higher education institutions still lacks clear standards. Additionally, educators lack the necessary competence to introduce students to new perspectives on entrepreneurial values. This community engagement aims to implement standardized entrepreneurship education in higher education institutions, focusing on the theme Best Practice – Business Startup Strategies for Students through the introduction of the effectuation concept and the business model canvas. The participants of this activity consist of 63 students and 5 lecturers from STIE YPUP Makassar. The outcome of this activity is the students' ability to apply these concepts to generate new business ideas. Seventeen groups were formed, and from these groups, three unique and feasible business ideas were selected. The implementation of this activity involved presentations, discussions, and mentoring. The significant impact of this community engagement is evident in the high level of enthusiasm and the creation of creative and innovative business ideas during the two-day training, serving as evidence of its success with the involved partners.